Application of the Problem Based Learning (PBL) Learning Model Using the Peer Tutor Method to Improve the Mathematical Problem Solving Ability of Class XI-1 Students at SMAN Madani Integrated Model - Arnisah, Sitti; Tajudin, Tajudin; Lefrida, Rita (CV. Rayyan Dwi Bharata, 2025)
This research aims to obtain a description of the application of the Problem Based Learning (PBL) learning model using the peer tutoring method to improve the mathematical problem solving abilities of class XI-1 students at SMAN Madani Integrated Model. The subjects of this research were 36 Madani Integrated Model SMAN students and 6 people were selected to serve as tutors and 3 people were selected as informants and 6 heterogeneous study groups were formed. The results of the research show that the application of the Problem Based Learning (PBL) learning model using the peer tutoring method can improve the mathematical problem solving abilities of class XI-1 students at SMAN Madani Integrated Model. This can be seen from the results of students' written tests which show that students' mathematical problem solving abilities have increased from cycle I to cycle II. Problem solving ability in cycle I had an average percentage of 55.56% which was classified as medium criteria, then in cycle II it increased to 82.63% which was classified as very high criteria. In the indicator of understanding the problem, it was found that the average percentage in cycle I was 61.11%, increasing to 83.33% in cycle II. In the indicator of making a problem solving plan, it was found that the average percentage in cycle I was 55.56%, increasing to 88.89% in cycle II. In the indicator of completing the problem solving plan, it was found that the average percentage in cycle I was 50.00%, increasing to 80.56% in cycle II. In the indicators for interpreting the results obtained, the percentage in cycle I was 55.56%, increasing to 82.63% in cycle II. Apart from that, students' classical learning completeness showed that there was an increase in the average score in cycle I, namely 71.94, increasing to 80.13. In cycle I, it showed that the percentage of students who achieved the KKM score was 72.22%, where students had not yet achieved the criteria for success in the action. Then in cycle II it increased to 91.67% so that the success indicator had been achieved.